1985
DOI: 10.1148/radiology.157.1.3898223
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous aspiration, drainage, and biopsies in children.

Abstract: Percutaneous aspiration, drainage, and biopsy techniques can be performed safely and effectively in infants and children. Over the past 4 years we performed 11 aspiration, nine drainage, and 14 biopsy procedures in patients aged 1 day to 17 years. Success was achieved in 88% and 93% of drainages and biopsies, respectively. Our experience suggests that aspiration and drainage procedures are effective in the diagnosis and management of fluid collections and are often the only procedure required and that percutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Percutaneous aspiration of intra-abdominal masses has been advocated as a safe, effective diagnostic procedure in the paediatric age group. 8 The cytology, combined with the ultrasound appearances, suggested the diagnosis in the present case. When subdiaphragmatic pulmonary sequestration is suspected on ultrasound examination, confirmation may be obtained with ultra-DAVIES ET AL 49 sound-guided fine-needle biopsy, allowing conservative management while asymptomatic.…”
Section: Discussionsupporting
confidence: 54%
“…Percutaneous aspiration of intra-abdominal masses has been advocated as a safe, effective diagnostic procedure in the paediatric age group. 8 The cytology, combined with the ultrasound appearances, suggested the diagnosis in the present case. When subdiaphragmatic pulmonary sequestration is suspected on ultrasound examination, confirmation may be obtained with ultra-DAVIES ET AL 49 sound-guided fine-needle biopsy, allowing conservative management while asymptomatic.…”
Section: Discussionsupporting
confidence: 54%
“…PCD is a very safe procedure for abscess drainage as well as for detecting pathogens, even when patients are aged and have poor conditions. [2021222324]…”
Section: Discussionmentioning
confidence: 99%
“…Imaging-guided percutaneous aspiration or drainage using sonographic guidance was first reported in 1974 in adults and now has been applied in children [6][7][8][9][10][11][12]. Tan et al [22] reported a series of six cases, three of whom were solitary abscesses that were treated by open drainage in two and antibiotics alone in one with good results.…”
Section: Discussionmentioning
confidence: 99%